Loss-of-function mutation of c-Ret causes cerebellar hypoplasia in mice with Hirschsprung disease and Down's syndrome - Ohgami, Nobutaka (J Biol Chem, 2021)
The c-RET proto-oncogene encodes a receptor-tyrosine kinase. Loss-of-function mutations of RET have been shown to be associated with Hirschsprung disease and Down's syndrome (HSCR-DS) in humans. DS is known to involve cerebellar hypoplasia, which is characterized by reduced cerebellar size. Despite the fact that c-Ret has been shown to be associated with HSCR-DS in humans and to be expressed in Purkinje cells (PCs) in experimental animals, there is limited information about the role of activity of c-Ret/c-RET kinase in cerebellar hypoplasia. We found that a loss-of-function mutation of c-Ret Y1062 in PCs causes cerebellar hypoplasia in c-Ret mutant mice. Wild-type mice had increased phosphorylation of c-Ret in PCs during postnatal development, while c-Ret mutant mice had postnatal hypoplasia of the cerebellum with immature neurite outgrowth in PCs and granule cells (GCs). c-Ret mutant mice also showed decreased numbers of glial fibers and mitogenic sonic hedgehog (Shh)-positive vesicles in the external germinal layer of PCs. c-Ret-mediated cerebellar hypoplasia was rescued by subcutaneous injection of a smoothened agonist (SAG) as well as by reduced expression of Patched1, a negative regulator for Shh. Our results suggest that the loss-of-function mutation of c-Ret Y1062 results in the development of cerebellar hypoplasia via impairment of the Shh-mediated development of GCs and glial fibers in mice with HSCR-DS.